A Trustworthy Data Sharing Solution for Dynamic Groups in the Cloud, Ensuring Security and Preventing Collusion - Kondragunta Rama Krishnaiah, Alahari Hanumant Prasad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Utilizing the advantages of cloud computing, users can now easily and cost-effectively share data among group members within the cloud. This process comes with low maintenance and management costs, making it highly convenient. However, ensuring the security of shared data is crucial, especially when outsourcing it to an untrusted cloud where collusion attacks can be a threat due to the dynamic nature of group membership. Presently, existing schemes rely on secure communication channels for key distribution, which is not always practical as these channels are not always available. To address these challenges, we have developed a secure data sharing scheme for dynamic groups. Our approach allows for key allocation without the need for secure communication channels, making it more feasible for practical use. Group administrators can securely provide private keys to users. Moreover, our scheme offers fine-grained entrance control, granting any user in the group access to the cloud-based resources, while effectively revoking access for users who are no longer part of the group. This way, former members cannot regain access by collaborating with the untrusted cloud, protecting the shared data from potential collusion attacks. Additionally, our method employs AES encryption during data processing, ensuring secure data sharing among cloud users. The storage overhead and encryption costs are minimal and scalable according to the number of users in the group. This ensures a protected multi-owner data sharing plan for dynamic groups in the cloud, with each user having the ability to safely share data with others. Our approach offers multiple levels of security for sharing data, accommodating various scenarios and group compositions. It guarantees that previous users do not need to update their private keys when new users join or when a user is revoked from the group. This efficiency ensures a smooth and seamless data sharing experience for all members involved.